DEVELOPING CRITICAL THINKING OF STUDENTS IN TEACHING A FOREIGN LANGUAGE - Ravshanova, Tursunoy (Журнал иностранных языков и лингвистики, 2022)
The article reveals the theoretical and methodological foundations for the development of students’ critical thinking in the process of teaching a foreign language and to substantiate the pedagogical conditions for its implementation. The author developed and substantiated a set of initial provisions that form the theoretical and methodological foundations for the development of students’ critical thinking in teaching a foreign language and revealed the essence and features of the development of critical thinking of students in the process of teaching a foreign language. The theoretical analysis made by the author on various aspects of the development and formation of critical thinking at the philosophical, social, psychological and pedagogical levels indicates the relevance of the problem and the interest of scientists in solving a number of identified problems.